Supported planar bilayers in studies on immune cell adhesion and communication. - Groves, J; Dustin, M (2003)
Supported planar bilayers have been used extensively in immunology to study molecular interactions at interfaces as a model for cell-cell interaction. Examples include Fc receptor-mediated adhesion and signaling and formation of the immunological synapse between T cells and antigen-presenting cells. The advantage of the supported planar bilayer system is control of the bilayer composition and the optical advantages of imaging the cell-bilayer or bilayer-bilayer interface by various types of trans-, epi- and total internal reflection illumination. Supported planar bilayers are simple to form by liposome fusion and recent advances in micro- and nanotechnology greatly extend the power of supported bilayers to address key questions in immunology and cell biology.